The concepts of the taxation of agricultural properties in the selected European countries – proposals for Poland - Burzec, Marcin (Instytut Rozwoju Wsi i Rolnictwa Polskiej Akademii Nauk, 2015)
In all countries belonging to the European Community on income derived from the agricultural activity is levied income tax. However lands and buildings used for agricultural activity are taxed by property tax. There is one exception in this matter, in Poland both ownership of agricultural land and income derived from agricultural activities are burdened by an outdated and inefficient agricultural tax. There is no doubt that in the case of future taxation in Poland, it will be necessary to redefine the rules for taxation of agricultural properties. The main aim of this article is to show the concept of taxation of lands and buildings used in carrying out of agricultural activities in the countries belonging to the European Union.
Keywords: tax; property tax; agricultural properties; European Community countries